Preliminary Investigation of Different Drying Systems to Preserve Hydroxytyrosol and Its Derivatives in Olive Oil Filter Cake Pressurized Liquid Extracts - Lucía López-Salas; Inés Cea; Isabel Borrás-Linares; Tatiana Emanuelli; Paz Robert; Antonio Segura-Carretero; Jesús Lozano-Sánchez (Foods, 2021)
Phenolic compounds present in extra virgin olive oil (EVOO) could be retained in its byproducts during processing. Among them, hydroxytyrosol and its derivatives deserve special attention due to their health benefits recognized by The European Food Safety Authority (EFSA). In the present research, the presence of these compounds in the filter cake byproduct was studied by combining pressurized liquid extraction (PLE) and high-performance liquid chromatography coupled to time-of-flight mass spectrometry (HPLC-TOF-MS). The applied optimum extraction parameters were 1500 psi, 120 °C and aqueous ethanol (50:50, v/v). The influence of different drying methods (vacuum-, freeze- and spray-drying) in the recovery of phenolic compounds was also evaluated. A total of 16 compounds from EVOO were identified in the extracts, 3 of them being hydroxytyrosol-related compounds, 6 substances of oleoside and elenolic acid derivatives, together with 6 secoiridoids and 1 lignan. The results highlighted the great number of phenolic compounds recovered from filter cake with these techniques, being even higher than the reported content in EVOO and other byproducts. The combination of PLE and freeze-drying resulted in being the best procedure for the recovery of phenolic compounds from filter cake byproduct.